'We Have Everything to Learn from the Americans': Film Promotion, Product Placement and Consumer Culture in Italy, 1945-1965. Issue 1 (2nd January 2020) - Gundle, Stephen
Abstract : The relationship between film promotion and the wider economy has scarcely been studied in Italy. This article explores the influence of American exploitation techniques in the peninsula in the years following World War Two and the responses of the Italian film industry. It is shown that, though many advocated imitating American practices in the fields of advertising and promotion, over time the industry learned not only to appropriate successful techniques but to adapt them in ways that were better suited to products that were often presented as being more 'cultural' than 'commercial'. Attention is paid to the way film directors were drawn into campaigns to underline the cultural value of their works. By the same token, Italian stars were not cast as cheerleaders for the developing consumer economy in the way that American stars had been. Yet linkages between film making and advertising were nevertheless forged through practices of product placement that exploited the loophole of 'verisimilitude'. Hollywood runaway productions like Roman Holiday set the tone for the insertion of Vespa scooters, automobiles and other goods in feature films. The article evaluates the interplay of the cultural and the commercial in Italy's postwar economic revival and the role of cinema in its development as a mass consumer society.